The role of the Islamic education teacher in developing the values of moderation and moderation among secondary school students in Jeddah - Alomari, Fahad Ahmed; Akram, Habba Ahmed (Journal of Curriculum and Teaching Methodology, 2023)
The study aims to identify the role of the Islamic education teacher in developing the values of moderation among high school students in Jeddah. The researcher used the Descriptive survey approach, and the sample consisted of 36 Islamic education supervisor and 131 high school Leaders. The questionnaire was prepared to achieve the objectives of the study. It included 53 sentences divided into (planning, implementation, and evaluation). The questionnaire was validated for validity and reliability. The results showed that there are statistically significant differences at (0.05) between the average responses of school leaders and secondary education supervisors in determining the role of the Islamic education teacher in developing the moderation values in (planning, implementation and evaluation) of secondary school students. The role of the Islamic education teacher in developing moderation values in statistical methods (3.91) indicates that Islamic education teachers at the secondary schools play an effective role in developing moderation values. The study recommended, among other things, to promote the values of moderation derived from the teachings of Islam. Educational officials who are leaders of Islamic schools and supervisors should be concerned with the values of Islamic education, and they must know to what extent an Islamic education teacher applies these values.
Keywords: The role of the Islamic education teacher; moderation; secondary school students; Jeddah city